Análise de desempenho e comportamento de wetlands horizontais de fluxo subsuperficial baseado em modelos hidráulicos e cinéticos - Andre Cordeiro De Paoli (2010)
This study aimed to evaluate the performance and behavior of two constructed wetlands (WC) horizontal subsurface (planted - WP and unplanted - WNP) as post-treatment of UASB reactor treating domestic wastewater equivalent to a population of 50 inhabitants each. The performance on the quality of the effluent, which was monitored for two years, showed excellent results concerning the removal of organic matter and solids, with global average efficiencies for the parameters BOD5 and TSS of 94 and 98% for WP and 93 and 98% for WNP, respectively. The presence of plants was more significant in the removal of NTK (WP: 39% and WNP: 29%) and E. coli (WP: 99.99% and WNP: 99.9%). After a year of operation was observed unwanted surface flow at the beginning of the bed, and in order to understand the causes of this process that may compromise the performance and applicability of these systems, some studies on the wetlands hydrodynamics have been conducted. Comparative results are presented related to quantification and characterization of accumulated solids and hydraulic conductivity located along the beds. It was noted that the WP accumulates / produces more solid, especially volatile, which gives lower hydraulic conductivity compared to WNP. Studies with tracer element were performed to clarify these and other questions, such as the hydraulic retention time and the actual type of the mainstream systems. More representative values of variables that describe the kinetics of removal organic matter along these systems, especially as regards to tropical conditions. This decay profile of organic matter associated with the type of predominant flow allowed to obtain dimension parameters of these units that are more appropriate. The obtained results indicate the possibility of reducing the WC dimensions, without reducing the efficiency of removing organic matter. More compact system allows for greater application and dissemination of technology due to a reduction of required area and deployment costs.